Development of a system for X-ray analysis within the mining industry - Estrada Calderon, Efrain; Zagerholm, Isac (My University, 2012)
Companies within the mining industry perform exploration drilling (prospecting) in order to find new mineral resources. The prospecting results in a lot of rock samples which are analyzed to discover what minerals they may contain. Today's analysis process involves high investments, high risks, and is very time inefficient. A start-up company called Minalyze is developing a product that will be capable of analyzing rock samples using X-ray.The product will be used at the drill site, and will involve much lower investments and very short analysis times.The purpose of this thesis is to design and develop Minalyze's first functional prototype called Minalyzer SCS. The aim is to implement different hardware components into a device that follows a concept which Minalyze has developed. Furthermore, a software architecture for controlling the hardware with a PLC will be developed, as well as a software architecture for controlling the PLC, from a PC, using LabView. During this thesis a partial vertical prototype was developed. The required hardware components required were identified, and a safety system was implemented. The PLC software, which consist of a series of programs and functions that control the actuators and performs data acquisition, was developed. Finally, for the software in LabView, a layered system design was used, together with an OPC system for exchanging data between the PLC and LabView. This thesis shows the importance of developing a prototype in an early stage of a product development process, for optimizing the product based on feedback received from investors,clients, and the development team. Prototyping also helps increasing the value of a start-up company. The result of the thesis is that Minalyze now owns two functional SW architectures, in LabView and the PLC, and functional hardware, ready to be implemented with a graphical user interface. When the company has completed the remaining drivers for the X-ray generation components (including a high-voltage generator and a X-ray detector), and developed the graphical user interface, the prototype will be ready to be shown for investors and customers. It will greatly aid Minalyze in the development of their final product.
Keywords: Människa-datorinteraktion (interaktionsdesign); Informations- och kommunikationsteknik; Human Computer Interaction; Information & Communication Technology